Empowering social innovators through collaborative and experiential learning - Pappas, Ilias O.; Mora, Simone; Jaccheri, Letizia; Mikalef, Patrick (2018 IEEE Global Engineering Education Conference (EDUCON), 2018)
Educating social innovators in higher education is of great importance as many societal challenges exist. This study combines experiential learning with ICT tools to provide students with the needed competences and experiences to solve societal challenges. We employ this approach in an innovative course, named Experts in Teamwork (EiT), which follows the experiential learning cycle. The participants of this study are undergraduate students interested to learn how they can solve societal challenges. Specifically, 26 students with various background and nationalities participated. A collaborative platform was developed that supports teamwork and cooperation, as well as the social innovation process. The findings show that this approach can influence positively learning outcomes and increase students' engagement and motivation with both social innovation and the learning process. Also, students' creativity was increased leading to the development of better solutions. The overall outcomes contribute to theoretical and practical development, to allow educators to take appropriate measures to enhance students' learning experience and foster social innovation through ICT.
ISSN: 2165-9567
Keywords: Réservé UdeM; Rôle des universités

Empowering social innovators through collaborative and experiential learning - Pappas, Ilias O.; Mora, Simone; Jaccheri, Letizia; Mikalef, Patrick (2018 IEEE Global Engineering Education Conference (EDUCON), 2018)
Educating social innovators in higher education is of great importance as many societal challenges exist. This study combines experiential learning with ICT tools to provide students with the needed competences and experiences to solve societal challenges. We employ this approach in an innovative course, named Experts in Teamwork (EiT), which follows the experiential learning cycle. The participants of this study are undergraduate students interested to learn how they can solve societal challenges. Specifically, 26 students with various background and nationalities participated. A collaborative platform was developed that supports teamwork and cooperation, as well as the social innovation process. The findings show that this approach can influence positively learning outcomes and increase students' engagement and motivation with both social innovation and the learning process. Also, students' creativity was increased leading to the development of better solutions. The overall outcomes contribute to theoretical and practical development, to allow educators to take appropriate measures to enhance students' learning experience and foster social innovation through ICT.
ISSN: 2165-9567
Keywords: Réservé UdeM; Rôle des universités